Effect of Reflective Teaching on Basic Science Performance of Students in Ogbia Local Government Area, Bayelsa State - Chinda, Worokwu; Akpomiemie, Voke Lilian; Fredrick, Ataene Fredrick; Henry, Nkeechinyere Happiness (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2024)
This study examines the effect of reflective teaching on the academic performance of students in Basic Science in Ogbia Local Government Area, Bayelsa State. Quasi-experimental research design was adopted for the study. The population of the study comprises all JSS3 students in all public secondary schools in Ogbia Local Government Area of Bayelsa State with a sample size of 240 students which were purposively drawn from ten selected schools. The sample of students learning basic science was randomly assigned to a control group which was taught basic science using the traditional teaching strategy and an experimental group using reflective teaching. The instrument for data collection was the Basic Science Achievement Test (BSAT) The instrument was validated by giving to experts in the field of measurement and evaluation and science education, who ensure the face and content validity, the instrument has a reliability of 0.82 Kuder Richardson 21. A basic science achievement test (BSAT) was administered to both groups before and after treatment (pre-test and post-test). Data collected was analysed using descriptive statistics mean and standard deviation and the hypothesis was tested using a t-test and Analysis of Covariance (ANCOVA). Findings showed that students taught with reflective teaching methods performed slightly better than those taught using traditional methods. It also indicated that male students had a slightly higher improvement in academic performance compared to female students when taught using the reflective teaching method. It was concluded that reflective teaching has a slightly significant influence on the academic performance of students. Based on the conclusion, it was recommended among others that teachers should use a reflective teaching approach in teaching basic science as it improves the interest of students to study science.